Commoning (in) the neighborhood, righting the city: The role of participatory budgeting in enacting the right to the city through commoning in Lisbon - Pappa, A. (2024)
The pursuit of the Right to the City (R2C) calls for prioritizing the most affected by its absence [1]. Operationally, this denotes a two-way dynamic between the impact of bottom-up emancipatory practices on transforming institutional norms and the ability of top-down resources to reach and activate socially and spatially marginalized populations. This paper portrays the R2C within the pragmatical context of the participatory budget of BIP/ZIP in Lisbon, depicting it as a network of institutionally aided commoning activities performed in disadvantaged urban neighborhoods. Towards this goal, the study initially develops a framework for analyzing the R2C through commoning practices by aligning a taxonomy of activities in the BIP/ZIP projects with Susser and Tonnelat’s [2] rights to everyday urban life; encounter; and creative activity. The devised commoning framework encompasses activities that 1. Prioritize the most disadvantaged, 2. Promote social development, 3. Have a strong spatial character, 4. Practice togetherness and solidarity, 5. Enhance the value of the neighborhood and 6. Expand neighborhood boundaries. Subsequently, this framework is employed to analyze the BIP/ZIP projects and portray the pursuance of the R2C within the program by pinpointing emerging and under-addressed rights in BIP/ZIP neighborhoods. To accomplish these objectives, the study employs a mixed-method approach integrating theoretical exploration of urban commons and R2C, data collection and organization. This involves mapping a dataset of projects into attributes, qualitative coding cycles to categorize project activities into a commoning taxonomy, and subsequently utilization of this model for statistical data analysis.